Ondas gravitacionais em teorias de gravitação quadrática - Alves, Matheus Filipe Santos (2022)
The success of General Relativity in describing gravitational phenomena is unquestionable. Despite this, there are conceptual problems in General Relativity, such as the presence of singularities in solutions to the Einstein equation, energy and dark matter, in addition to the fact that the theory is not renormalizable, which makes it impossible to quantize it in a conventional way. One way to try to circumvent these problems is to use the so-called theories of modified gravitation. In the scope of this work we will focus our study on the quadratic gravitation model that has been receiving attention due to its application in the context of quantum gravity as it is a renormalizable theory. After a brief review of the theory of gravitational waves in General Relativity, the proposed gravitation is explored. The quadratic gravity field equations are deduced, linearized, and then solutions of these equations are studied. In addition, a detailed study of the degrees of freedom in this theory of gravitation is made. An analysis of the emission of gravitational waves by binary point black hole systems is also made and, in particular, we study the orbital dynamics and the waveform that would be observed by a detector. Finally, we compare the results with General Relativity and obtain constraints in the parameters of the theory.